Natural Area Weeds: Old World Climbing Fern (Lygodium microphyllum) - Kenneth A. Langeland; Jeffery Hutchinson (EDIS, 2013)
Native to Africa, Asia, and Australia, Old World climbing fern (OWCF) is a newcomer to Florida that has spread at an alarming rate since its introduction. The Florida Exotic Pest Plant Council considers Old World climbing fern to be invasive. It’s also regulated by laws of the Florida Department of Agriculture and Consumer Services (FDACS) as a Florida Noxious Weed and by the United States Department of Agriculture (USDA) as a Federal Noxious Weed. It may be the most serious threat to Florida’s natural areas. This 6-page fact sheet was written by Kenneth A. Langeland and Jeffery Hutchinson, and published by the UF Department of Agronomy, February 2013.